Learning Resource Center receives ITTPC (CRLA International Tutor Training Program Certification - Level One) (2024)
We are pleased to announce that the Learning Resource Center has been awarded certification as a Level One certified tutor training program by the internationally recognized College Reading and Learning Association (CRLA). This is a major accomplishment that reflects the LRC and CSUCI's commitment to student success.